THE APPLICATION OF BABADOTAN (AGERATUM CONYZOIDES, L) EXTRACT PGPR WITH DIFFERENT CONCENTRATIONS AND INTERVALS ON THE GROWTH AND YIELD OF TOMATO (LYCOPERCUM ESCULENTUM, MILL) - Olivina Sofia Messakh; Ester R. Jella (STMIK Widya Cipta Dharma, 2023)
This study aims to determine the effect of babadotan PGPR application with different concentrations and intervals on the growth and yield of tomato plants. This research was conducted at the Plant Production Laboratory, Department of Food Crops and Horticulture, Kupang State Agricultural Polytechnic in April-November 2021. The design used was a factorial randomized block design. The first factor was the PGPR concentration which consisted of 5 levels, namely 0 ml/L, 5 ml/L, 10 ml/L, 15 ml/L and 20 ml/L; while the second factor is the PGPR concentration interval which consists of 3 levels, namely 1, 2 and 3 weeks. Each factor was repeated three times so that the total number of experimental units was (5 x 3) x 3 = 45 experimental units. Observational variables of tomato growth include plant height, number of leaves and plant stem diameter. While the yield observation variables include the number of fruit and fruit weight of tomato plants. The data obtained were analyzed using the F test. If there were significant differences between the factors tested, then the analysis was continued with the BNT test. The results showed that the concentration of PGPR from babadotan extract 20 ml/liter with intervals every 2 weeks had a significant effect on plant height at 6 WAP and stem diameter at 6 MST. Differences in the concentration of PGPR in babadotan extract and the interval of application significantly affected the weight per fruit of tomato plants.